Pengaruh Penggunaan Media Macromedia Flash Terhadap Motivasi Belajar Siswa Kelas IV di SDN 2 Seteluk - Alfi Mashudi; Muhammad Tahir; Ilham Syahrul Jiwandono (Journal of Science Instruction and Technology, 2021)
This study aims to determine the effect of using Macromedia flash media on the motivation to learn Pancasila and Citizenship Education for fourth-grade students at SDN 2 Seteluk. This type of research is experimental research, Quasi-Experimental Design in the form of Nonequivalent Control Group Design. The population in this study were all fourth-grade students at SDN 2 Seteluk. Sampling using the Census / Total Sampling technique. The data collection methods were questionnaires and observation. The questionnaire was used to obtain data related to student learning motivation, while observation was used to obtain data on the implementation of learning using Macromedia flash media. Based on the results of the Independent Sample T-Test, a significance value or Sig (2-tailed) of 0,000 was obtained, which means less than 0.05. This shows that Ho is rejected and Ha is accepted, so it can be concluded that there is an effect of using Macromedia flash media on the learning motivation of the fourth-grade students of Pancasila and Citizenship Education at SDN 2 Seteluk.